Implementation of business process improvement project carried out at Nottinghamshire Healthcare National Health Service Trust (NHNHST) involving the real-time application of lean six sigma principles and Information Technology (IT) - Kamthan, Prateek (2015)
This dissertation demonstrates the implementation of a business process improvement project carried out at Nottinghamshire Health Care National Health Service Trust (NHNHST) involving the real-time application of lean six sigma principles and Information Technology (IT). The goal of project is to find a business solution that allows NHNHST to share and collaborate information using the HP Action Plan tracker (HPAPT) more efficiently and effectively in order to embed on-going learning within the Health Partnerships (HP) division. To achieve our goal, we utilised the DMAIC methodology of lean six sigma, where we have used tools such as project charter, business process maps, check sheets, time analysis, fish bone diagram, poka yoke and process flow logic. The main highlight of our approach was the out-of-box idea to interface and jointly use the DMAIC methodology with the waterfall model of software development life cycle. We also carried out primary research (face-to face interviews, telephonic survey, meetings and brainstorming with the Client team and end users) to document current system architecture, its gaps and user requirements. Secondary research (IT research reports from Gartner, Forrester, etc. and software product section of leading software companies such as Microsoft, IBM, Oracle, etc.) was conducted to identify the right software product that will deploy as the solution. Consequently, process re-design recommendations were given, which comprised the removal of non-value added activities such as sending manual notifications, duplication of tasks, manual version control and manual management of documents. This will also improve the quality of documents by elimination of data anomalies. The overall “To-be” design of the improved process was proposed to the Client. To materialise this design, Microsoft SharePoint as the content management software was identified, and has been already agreed with the Client for its deployment in the organisation. The Microsoft SharePoint software will enhance operations by bringing automation, real-time updatability, collaboration in work, automatic notifications and interactive user interface to the Client. To ensure the successful adoption of a business solution at both the individual and the organisational level, a change management strategy has been recommended to the Client that includes making effective communications through different media, providing hands-on training to employees and involving senior management support. The Client team has enthusiastically accepted the business solution. By implementing the business solution, NHNHST is anticipated to achieve per year cost savings of £35,700 and an 83% improvement in operational efficiency. However, the recommended solution will only operate till deployment of Microsoft SharePoint software and further work is required to create a solution for its maintenance, control and support phases.